THE READABILITY LEVEL OF READING TEXT IN ENGLISH TEXTBOOK ENTITILED “ BAHASA INGGRIS” FOR THE ELEVENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL - Bagus Krisdianto; Siti Aisah Ginting (Universitas Negeri Medan, 2022)
This study was aimed to find the readability level of reading texts in BahasaInggris textbook published by the Ministry of Education and Culture for the eleventhgrade of Senior High School of 2017 revised edition. This study is categorized as amixed method reseach which used the embedded design. It means that combines bothof qualitative and quantitative approach in one study. The data were collected byusing document analysis Flesch Reading Ease formula and Flesch Reading EaseScore were used as the instruments of this study to measure the readability level ofreading texts in Bahasa Inggris textbook of 2017 revised edition textbook. The resultof Flesch Reading Ease formula calculation was one text is in the Easy level; tworeading texts are in the Fairly Easy level; one text is in the Standard level; four textsare in Fairly Difficult level; and two reading texts are in the Difficult level. Thefindings of this study showed that from ten reading texts in Bahasa Inggris textbookof 2017 revised edition only four reading texts were readable for the eleventh gradestudents of Senior High School. They were which in Fairly Difficult level with scoreranged from fifty to sixty.